Premieren '85 : in 31 Kölner Galerien. - Galerie Inge Baecker, Köln; Baukunst-Galerie, Köln; Galerie Thomas Borgmann, Köln; Galerie Dreiseitel, Köln; Galerie Gugu Ernesto, Köln; Anna Friebe Galerie, Köln; Galerie Friedrich, Köln; Galerie Glöckner, Köln; Galerie Gmurzynska, Köln; Galerie Karsten Greve, Köln; Galerie Tanja Grunert, Köln; Galerie Max Hetzler, Köln; et al. (Köln : Stadt Köln, 1985)
Van Velde, Bram ; Frank, Edvard ; Léger, Fernand ; Knöller, Paco ; Mullican, Matt ; Büttner, Werner ; Tischler, Reinhard ; Steiger, Dominik ; Cürten, Gregor ; Jahn, Justus ; Dokoupil, Jiri Georg ; Yilmaz, Adem ; Lambertin, Theo ; Herkenrath, Peter ; Walther, Franz Erhard ; etc.
Premieren '85 in 31 Kölner Galerien, Stadt Köln, 26. + 27.4.'85
boek